The Effect of Substrate Type on Vegetation Density Rhizopora Mucronata in Gampong Iboih Sabang: The Effect of Substrate Type on Vegetation Density Rhizopora Mucronata in Gampong Iboih Sabang - Bakruddin - (Jurnal Celebica : Jurnal Kehutanan Indonesia, 2023)
As a coastal area, Gampong Iboih Sabang has the potential for biological resources such as a mangrove forest which is quite wide of around 23 hectares. However, most of the mangrove area has been subject to illegal logging and one of its functions has been converted into ponds, so it is very vulnerable to ecosystem damage. This study aims to determine the relationship between the type of substrate and the density of Rhizophora Mucronata vegetation in the village of Iboih Sabang. The research was conducted at the fishermen's center using the checkered line method. The placement of the transect line is perpendicular to the coastline seaward with a transect length of 250 m. The number of transects made was 4 with a distance of 50 m between transects. Along the transect Place 16 plots. The results showed that the density of Rhizophora mucronata at the tree level was 45.31% and from the results of routine soil and water analysis Rhizopora mucronata was able to live on muddy and sandy substrates. The condition of the environmental parameters at the study site was good for the growth of Rhizophora Mucronata mangroves.